Balanites aegyptiaca (L.) Delile: a review of its traditional uses, phytochemistry and biological activities - A.S. Shinde; V.V. Ingole; S.P. Rasale; S.R. Katade (Phytomedicine Plus)
Background: Balanites aegyptiaca, a member of the Zygophyllaceae family, has been utilized in traditional Ayurvedic medicine for over 4000 years. Various parts of B. aegyptiaca have been employed to treat a wide range of ailments, including leprosy, worm infections, ulcerations, leukoderma, anorexia, constipation, fever, diarrhea, dysentery, whooping cough, and dermatological conditions. Purpose: This review outlines recent advancements in phytochemical databases and research on the Balanites aegyptiaca, emphasizing their chemical profiles, pharmacological potential, traditional applications, and molecular docking. It identifies current research gaps and offers insights to guide future studies in herbal drug development. Method: The literature survey was conducted using databases from 1913 to 2025, including Google Scholar, Web of Science, Embase, CINAHL, PubMed, and Library Journal. Result: Analysis revealed the presence of more than 84 distinct physiologically active compounds, including 14 phenolics, 14 flavonoids, 2 coumarins, 3 alkaloids, 8 steroids, 2 pregnane glycosides, 10 coumarin saponins, and 31 furostanol saponins. These bioactive compounds contribute to a broad range of the plant's pharmacological profile, which includes antioxidant, wound healing, antimicrobial, anti-hepatitis, anticancer, anti-inflammatory, molluscicidal, anticonvulsant, antiplasmodial, antiparasitic effects, androgenic properties, and molecular docking. Toxicological studies have also confirmed the safety of B. aegyptiaca for medicinal purposes. Conclusion: Balanites aegyptiaca exhibits significant pharmacological potential due to its rich phytochemical composition and traditional medicinal value. Continued scientific exploration may lead to its integration into modern therapeutic applications and novel drug formulations.